2001
DOI: 10.1098/rspb.2001.1774
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis reveals the wild ancestors of the llama and the alpaca

Abstract: The origins of South America's domestic alpaca and llama remain controversial due to hybridization, near extirpation during the Spanish conquest and di¤culties in archaeological interpretation. Traditionally, the ancestry of both forms is attributed to the guanaco, while the vicu·a is assumed never to have been domesticated. Recent research has, however, linked the alpaca to the vicu·a, dating domestication to 6000^7000 years before present in the Peruvian Andes. Here, we examine in detail the genetic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
1
31

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(169 citation statements)
references
References 22 publications
6
131
1
31
Order By: Relevance
“…However, recent DNA marker analyses have demonstrated that, while the llama (Lama glama) has been domesticated from guanacos, the alpaca is descended from the vicuña, and should be classified as Vicugna pacos (Kadwell et al 2001). The selected alpaca VHH domains show good sequence homology to the known VHH domains from other camelids; for instance the protein sequence of TVX72 is 80% identical to that of a L. glama VHH domain (accession CAD22462).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent DNA marker analyses have demonstrated that, while the llama (Lama glama) has been domesticated from guanacos, the alpaca is descended from the vicuña, and should be classified as Vicugna pacos (Kadwell et al 2001). The selected alpaca VHH domains show good sequence homology to the known VHH domains from other camelids; for instance the protein sequence of TVX72 is 80% identical to that of a L. glama VHH domain (accession CAD22462).…”
Section: Discussionmentioning
confidence: 99%
“…They have documented its phylogenetic relationships and domestication using mtDNA and microsatellite markers (Stanley et al, 1994;Kadwell et al, 2001;Palma et al, 2001), its molecular evolution (Lin et al, 2001;Maté et al, 2004), the variability in allozymes (Norambuena and Paredes, 2003) and the phylogeography and population genetics of wild populations across Chile and Bolivia (Sarno et al, 2004). Here, we present a geographically comprehensive assessment of the molecular diversity of the species, focusing on the mtDNA CR.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial (mt) DNA sequence data indicate a divergence of at least two million years between vicuñ a and its wild (and more altitudinally flexible) relative the guanaco (Lama guanicoe; Stanley et al, 1994;Kadwell et al, 2001). Palaeontological evidence suggests that the genus Vicugna evolved from Hemiauchenia in the lowlands east of the Andes as early as two million years ago (Webb, 1974;Harrison, 1979), although a revision of some of this material led Menegaz et al (1989) to conclude that the vicuñ a evolved from the guanaco at the beginning of the Holocene.…”
Section: Introductionmentioning
confidence: 99%
“…Kadwell et al (2001) mostraron que hay una alta similitud genética entre alpaca y vicuña y entre llama y guanaco estudiando ADN mitocondrial y ADN microsatélite. Sus datos estarían de acuerdo con estudios recientes que postulan que en los camélidos sudamericanos no existirían 4 especies claramente separadas (Marin et al, 2007a).…”
Section: Valenzuela-estrada M; Rippes F and Nuñez Hunclassified